Comparatively Evaluating the Role of Herb Pairs Containing Angelicae Sinensis Radix in Xin-Sheng-Hua Granule by Withdrawal Analysis. (22nd September 2020) - Pang, Han-Qing; Xu, Ding-Qiao; Tang, Yu-Ping; Zhou, Gui-Sheng; Xu, Hui-Qin; Jin, Yi; Zhu, Zhen-Hua; Shi, Xu-Qin; Yue, Shi-Jun; Chen, Yan-Yan; Huang, Sheng-Liang; Duan, Jin-Ao
Abstract : The present study aims to investigate the roles of herb pairs containing Angelicae Sinensis Radix (Danggui) in Xin-Sheng-Hua Granule (XSHG) on hemolytic and aplastic anemia (HAA) mice. HAA model mice were induced by acetyl phenylhydrazine and cyclophosphamide; then the samples of XSHG and its decomposed recipes (DY, DC, DT, DH, DJ, and DZ) were orally administrated to these mice. Indicators of peripheral blood routine, organ index, and ATPase activities were tested. Moreover, the main effective components in these samples were also analyzed by UHPLC-TQ-MS/MS. Clear separation between the control and model groups from score plot of principal component analysis (PCA) was easily seen, indicating that HAA model was successfully conducted. Afterwards, relative distance calculation method between dose groups and control group from PCA score plot was adopted to evaluate the integrated effects of hematinic function of different samples. And the orders of hematinic effects were as follows: XHSG > DJ > DT > DZ > DH > DC > DY. Further analysis of these samples by UHPLC-TQ-MS/MS revealed that XSHG underwent complicated changes when herb pairs containing Danggui were excluded from XSHG, respectively. Compared with XSHG, the vast majority of active compounds in sample DY (formula minus herb pair Danggui-Yimucao) decreased significantly, which could partly explain why herb pair Danggui-Yimucao made great contribution to XSHG. These findings showed that withdrawal analysis method is a valuable tool to analyze the impacts of herb pairs containing Danggui on XSHG, which could lay foundation to reveal the compatibility rules of this formula.